2012
DOI: 10.14710/jitaa.37.1.1-9
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Microsatellite Markers to Study Genetic Diversity in Indonesian Sheep

Abstract: ABSTRAKTujuan penelitian ini adalah mempelajari keragaman genetik populasi domba di Indonesia menggunakan penciri DNA mikrosatelit. Sebanyak 18 lokus DNA mikrosatelit digunakan untuk menentukan genotipe populasi domba Indonesia. Sampel darah domba yang digunakan sebanyak 200 ekor berasal dari populasi domba garut tipe tangkas, domba garut tipe daging, domba purbalingga, domba batur dan domba jember diektraksi DNA total dengan menggunakan metode salting out. Data lokus DNA mikrosatelit dianalisis menggunakan pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
5
11
2
Order By: Relevance
“…However, a higher number of alleles for each locus showed that all the markers used were appropriate to analyze diversity in studied breeds. The level of variation depicted by number of alleles at each locus was similar to earlier reports on sheep breeds (Arora and Bhatia, 2006;Jakaria et al, 2012;Hepsibha et al, 2013;Crispim et al, 2014). Among the types, the mean of PIC ranged from 0.72 in LRB-PAK to 0.88 in ARB, and Shannon information index ranged from 1.58 in KER-PAK to 2.27 in ARB.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, a higher number of alleles for each locus showed that all the markers used were appropriate to analyze diversity in studied breeds. The level of variation depicted by number of alleles at each locus was similar to earlier reports on sheep breeds (Arora and Bhatia, 2006;Jakaria et al, 2012;Hepsibha et al, 2013;Crispim et al, 2014). Among the types, the mean of PIC ranged from 0.72 in LRB-PAK to 0.88 in ARB, and Shannon information index ranged from 1.58 in KER-PAK to 2.27 in ARB.…”
Section: Discussionsupporting
confidence: 88%
“…This can be attributed to the excess of heterozygote individuals than homozygote individuals, migration, high mutation rate in microsatellite, artificial selection in all breeds and population subdivision owing to genetic drift (Aminafshar et al, 2008). Deviation from HWE at microsatellite loci has also been reported in various studies (Esmaeilkhanian and Banabazi, 2006;Banabazi et al, 2007;Nanekarani et al, 2010;Jakaria et al, 2012;Hepsibha et al, 2013;Crispim et al, 2014). It is known that a population is considered to be in HWE only when it is able to maintain its relative allelic frequencies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The number of alleles per locus for the three breeds studied ranged from 7 to18, indicating of genetic polymorphism within the tested Mahmoud et al 175 sheep populations. This range was comparable with that observed (6-18) in four Romanian sheep populations (Kevorkian et al, 2010;Jakaria et al, 2012). It was higher than that observed by Pramod et al (2009) in Vembur sheep population of South India (2-9) and by Radha et al (2011) in Kilakarsal sheep population (3-12).…”
Section: Discussionsupporting
confidence: 88%
“…The mean observed heterozygosity values in the present study were 0.895, 0.938 and 0.719 for SW, BR and NJ sheep breeds, respectively, with a grand mean of 0.851. This value is higher than that reported by other studies of Indonesian sheep (0.574), Coimbatore sheep in India (0.625) Turkish sheep (0.66) and Colombian sheep (0.680) (Jakaria et al, 2012;Hepsibha et al, 2014;Yilmaz et al, 2015;Ricardo et al, 2016, respectively). On the other hand, the expected heterozygosity (He), the best estimator of genetic diversity in a population (Kim et al, 2002), was 0.782, 0.741 and 0.716 for SW, BR and NJ sheep, respectively, with a grand mean of 0.746.…”
Section: Discussionmentioning
confidence: 51%